Dinamika bahasa anak usia dini: Bahasa Indonesia, daerah, asing, dan gaul di era modern - Chaniago, Ikwal Pangsa (Maliki Interdisciplinary Journal, 2024)
Language has a crucial role in children’s development, especially at the elementary school level. Children at this stage are introduced to various types of languages, including Indonesian as an official language, regional languages ​​as a local cultural identity, foreign languages ​​to open international horizons, and slang that reflects everyday communication. This research uses literature review and observation methods to analyze children’s language development. The research results show that children’s language development is currently influenced by internal and external factors. Internal factors include one’s ability to choose the right words and intonation. External factors include parental attention, learning environment, and play environment. The positive impacts of language development in the digital era and globalization include easy access to learning resources and information, while the negative impacts include a decrease in the quality of communication and exposure to inappropriate language. It is important for educators, parents and the community to provide appropriate assistance and monitoring regarding children’s language use in order to optimize positive impacts and minimize negative impacts. Observations and interviews show that children’s language use today is very diverse, with significant influence from technology and the surrounding environment.